Periosteal Ewing Sarcoma in a 65-Year-Old Man: A Case Report. Issue 2 (April 2017) - Bedard, Julia; Burns, Jessica; de Comas, Amalia
Abstract : Case: Ewing sarcoma is predominantly a pediatric bone malignancy involving the medullary canal. Periosteal Ewing sarcoma, a subtype arising from the periosteum, is exceedingly rare, with approximately 30 reported cases in the literature. We describe a case of periosteal Ewing sarcoma in the tibia of a 65-year-old man. Magnetic resonance imaging revealed a heterogeneous mass in the proximal tibial diaphysis without medullary involvement. The diagnosis was confirmed histologically after biopsy. The patient was treated with neoadjuvant chemotherapy, radical resection, and adjuvant chemotherapy. Conclusion: To the best of our knowledge, this case report describes the oldest documented patient with periosteal Ewing sarcoma.